Parkour – at skabe steder med kroppen - Larsen, Signe Højbjerre (Forum for Idræt, 2013)
Parkour – a placemaking practice Parkour is a relatively new movement-culture that has evolved rapidly in Denmark since 2005. In the academic field of scholarly work on parkour the movement-culture has been interpreted as a subversive bodily strategy for the subject to handle architecture, space and power. The movements of the traceurs are being ”read” for their cultural significance on a discursive level. The traceurs does not follow the social norms for how to move in public places, but balances on the back of benches, jumps over rails and crawls down stairs. In Denmark the interpretation of the movements of parkour as a critical practice meets oppositions. The first specialized facility for parkour was built in 2007 in cooperation with both the peoples academy ”Gerlev Idrætshøjskole” and practitioners of parkour. Today over 47 facilities for parkour exist. A problem lies within present studies’ point of departure which stems from abstract ideas about the city and political resistance instead of departuring in the bodily practice. What do the practioners actually do, when they practice parkour? This article seeks to answer this particular question and tries to do so based on the authors own experience and ethnographic fieldwork with practitioners in their daily training. Parkour is played out in the streets as well as in specialized facilities. What binds these places together and constitute parkour as a movement-culture, is a dynamic pattern of movements and a practical knowledge about the spatial and adaptive dimensions of these. These movements and the knowledge are incorporated into the bodies of the practitioners. By utilizing a theory of affordance by James Gibson and Polanyi’s concept of tacit knowledge the dynamic pattern can be understood as perceptual skills that opens up a new relation to the surroundings; in urban spaces as well as specialized facilities.